2018
DOI: 10.1136/vr.104987
|View full text |Cite
|
Sign up to set email alerts
|

‘Care about my animal, know your stuff and take me seriously’: United Kingdom and Australian clients’ views on the capabilities most important in their veterinarians

Abstract: Success in veterinary practice requires careful balancing of stakeholder needs. The aim of this study was to investigate the current expectations and needs of veterinary clients across a range of practice types. Interviews and focus groups were undertaken with veterinary clients to identify the capabilities of veterinarians that result in the best client experience, generating a 'Veterinary Capability Framework'. This comprised six main capabilities each containing 4-10 behavioural indicators: client relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Empirical findings also confirm that veterinary clients support the notion that it is the role of the veterinarian to advocate in the patient’s best interests. Thus, Hughes and colleagues found in their study of British and Australian clients that animal owners consider a commitment to the patient’s welfare and quality of life to be the most important goal that veterinarians should pursue [32]. However, a question arises about the extent to which professionals can adhere to such normative demands under everyday clinical circumstances [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical findings also confirm that veterinary clients support the notion that it is the role of the veterinarian to advocate in the patient’s best interests. Thus, Hughes and colleagues found in their study of British and Australian clients that animal owners consider a commitment to the patient’s welfare and quality of life to be the most important goal that veterinarians should pursue [32]. However, a question arises about the extent to which professionals can adhere to such normative demands under everyday clinical circumstances [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The authors point out that client needs and wants may vary according to the type of animal owned, the reason for the visit (routine healthcare versus emergency, for example) and difering opinions about what constitutes animal welfare. 1 In conclusion, the study found that veterinary clients valued veterinarians who displayed Farm animal-owning clients prioritised commitment to quality and the profession while small animal-owning clients prioritised commitment to animal welfare commitment to animal welfare and a high standard of veterinary care; were compassionate, open, honest and able to provide clear explanations; and inspired conidence in their skills and knowledge while balancing competence, professionalism and humanity. Taking inspiration from Maslow's hierarchy of needs, 19 Hughes and others created a hierarchy of client needs (their Fig 2).…”
Section: What You Need To Knowmentioning
confidence: 84%
“…These were: Hughes and others list four to 10 speciic behavioural indictors beside each capability (see their Table 1). 1 It may be useful for veterinary schools to consider this list, alongside the RCVS Day One competences, 12 when designing curricula.…”
Section: What Do Clients Want In a Veterinarian?mentioning
confidence: 99%
See 2 more Smart Citations